Nanoparticle-nanoparticle interactions and light-matter interaction studied by simulated absorption spectroscopy - Liu, Zhen (Kansas State University, 2023)
Plasmonics is one of the most important features of nanoparticles and other materials. Understanding plasmon interactions, plasmon-induced excitation energy transfer, and excited state dynamics of molecular plasmons are goals of this thesis. Utilizing efficient tight-binding calculations, the absorption spectra of homodimer and heterodimer nanoparticles are explored. Then, plasmon-induced excitation energy transfer is simulated with an attosecond time step up to investigate processes occurring on the picosecond dynamics time scale. Third, the naphthalene molecule, which has a molecular plasmon, is studied by simulated transient absorption spectroscopy using real-time time-dependent density functional theory calculations. Finally, nanoclusters Au₂₅ and Au₃₈ are also studied by ab initio transient absorption spectroscopy calculations. This dissertation represents the first time that atomically precise nanoclusters are explored by simulated ultrafast spectroscopy. In this thesis, we systematically study the nanoparticle homodimer and heterodimer interaction and analyze the peak shifting observed in absorption spectroscopy. As the interparticle distance decreases, the red shifting peaks originate from excitations with transition dipole moments along the z-axis with nondegenerate features. Conversely, the blue shifting peaks arise from excitations with transition dipole moments in the x and y direction with double degeneracy. The energy transfer between two nanoparticles has also been studied. Different energy transfer patterns as a function of different interparticle distances are explored. At relatively long distances, the energy transfer from one nanoparticle to another becomes more efficient as the interparticle distance decreases. However, at short distance, back-transfers of energy are observed, which reduces the dimer’s ability to accept energy from the electric field. The back-transfers also reduce energy transfer between nanoparticle dimer. Simulated transient absorption spectroscopy is performed to study naphthalene in order to explore the electron dynamics that occur after the plasmon peak is excited. With the help of electronic structure analysis, transient absorption signals below 3.5 eV are explored. Finally, we present a study of excited state dynamics of Au₂₅ and Au₃₈ by simulated transient absorption spectroscopy. With the help of orbital symmetry from ground state calculations, the electron and hole excitations in the simulated pump-probe experiment can be distinguished. Because of the nanorod-like shape of Au₃₈, different energies and directions of the pump laser are applied to Au₃₈ to induce absorptions polarized in different directions. This work provides an opportunity to compare isotropic nanoclusters such as Au₂₅ with anisotropic ones such as Au₃₈.
Keywords: Nanoparticle; DFT; Transient absoprtion